A COLLABORATIVE STUDY IN IMPROVING COMPETENCY IN SPEAKING SKILL BY USING “JAZZ CHANT TECHNIQUE” OF THE STUDENTS GRADE FIVE AT SD NEGERI 2 BANJAR TEGAL SINGARAJA - Artini, Ni Nyoman Sri (Yavana Bhasha : Journal of English Language Education, 2018)
The recent study was conducted to improve the competence of the students gradefive of SD Negeri 2 Banjar Tegal Singaraja in speaking capability by applying Jazz ChantTechnique. The subjects of the study were the second-year students of SD Negeri 2 BanjarTegal Singaraja, especially those who belong to class V. The total number of the subjects was17 students, 10 males, and 7 females. This study was conducted in two cycles. Each cycleconsisted of two sessions. The first sessions were done for the treatment and the last sessionwas for posttest. This study was an action-based classroom research that was conducted intwo cycles in which four steps were involved in each cycle, namely; planning, action,observation, and reflection. Besides, the data were obtained through three kinds of aninstrument; questionnaire, test, and researcher’s diary. A pre-test was given to the studentsbefore conducting the action to obtain the preliminary data of the students’ achievement inspeaking capability. Then, the data obtained were descriptively analyzed. The studyshowed that the students’ competence in speaking capability improved. The continualimprovement took place in the students’ achievement. It was shown by the students’ meanscore, which increased from cycle to cycle. Students’ mean score was 54 in the pre-test, whichwas categorized as poor. After the treatment was conducted, it increased to a sufficient levelof mastery 65 in post-test I. The second treatment was then conducted to get a satisfactoryresult since the results of students’ score were not satisfying yet. Finally, the students’ meanscore could reach a good criterion, which was 80 in the post-test II. From the observation, itwas found that Jazz Chant Technique allowed the students to collect their ideas, practicetheir pronunciation, intonation and organized their speaking capability through the song ofJazz Chant Technique that guided the students systematically in speaking capability so thatthey could produce good pronunciation in speaking. In addition, the technique also broughtabout a positive effect in fostering students’ motivation and interest in learning English.